Application techniques of a novel hemostat in cardiac operations: HEMOBLAST. Issue 9 (26th July 2019) - Bruckner, Brian A.; Ngo, Uy; Ramchandani, Mahesh; Suarez, Erik; Awad, Samir; Reardon, Michael
Abstract: Background: Postoperative bleeding complications are associated with less favorable outcomes in cardiac surgery and contribute to excessive overall healthcare costs. HEMOBLAST (Biom'up, Lyon, France) (HB) is a novel ready‐to‐use hemostatic powder that consists of porcine collagen, bovine chondroitin sulfate, and human pooled plasma thrombin that may help reduce surgical bleeding. Aims: The aim of this study was to describe the techniques of application for this new combination powder‐based hemostat, HB, and demonstrate its use employing photographs of application methods during cardiac procedures. Materials and Methods: The initial 24 procedures in which HB was used at our institution included: left ventricular assist device (LVAD) insertions, lung transplants, heart transplants, aortic valve replacements, coronary artery bypass grafting, and mitral valve repair. Results: Hemostasis was achieved in all cases and there were no instances of mediastinitis, sternal infections, allergic reactions, or 30‐day mortality. Discussion: This report describes the best methods of application of HB including use for treatment of mediastinal bleeding in a re‐operative procedure in a patient on antiplatelet agents and sternal bleeding during an LVAD insertion. Proper application can facilitate excellent hemostasis using this powder. Conclusion: HB is a novel powder‐based multiple component hemostatic agent that promotes focal or large area hemostasis. We have presented the techniques of use that are important to the successful application of HB to facilitate hemostasis.